Correlation of the Complement Decay Accelerating Factor, Tumour Necrosis Factors-alpha, and Interleukin-1 Beta with the Response to Rituximab in Rheumatoid Arthritis Patients - Haidar Mohammed Hussein; Ali Abdulhussein Kasim (Iraqi Journal of Pharmaceutical Sciences, 2025)
Rituximab (RTX) is one of the biological medications that has been used in the treatment of autoimmune diseases and cancer. However, a high percentage of patients may experience resistance to RTX therapy. The study aims to investigate the potential association of serum levels of the complement decay accelerating factor (DAF), as well as the pro-inflammatory cytokines, tumour necrosis factor-alpha (TNF-α) and interleukin-1 Beta (IL-1β); with response to RTX treatment in rheumatoid arthritis patients. A cross-sectional study was conducted under specialized physician supervision in the Specialized Center of Rheumatology at Baghdad Teaching Hospital in Baghdad/Iraq. Ninety adult patients who were already diagnosed with rheumatoid arthritis and receiving RTX intravenous infusion, for at least six months, were enrolled in the study. The selected patients were either responders to RTX (45 patients), or non-responders to RTX (45 patients). The response to RTX was assessed according to the 28-joint Disease Activity Score (DAS28). The serum level of the DAF was significantly higher in RTX non-responders in comparison to RTX responders, (P-value ˂0.001). Similarly, serum levels of TNF- α and IL-1β, were significantly higher in RTX non-responders in comparison to RTX responders, (P-value ˂0.001; for each). The serum level of the estimated markers showed a high significant correlation with the 6 months change in DAS28 (P-value ˂0.001; for each). The Cut-off values, sensitivity, and specificity of DAF, TNF-α, and IL-1β in identifying responders to RTX were (≤417.58 µg/L, 97.8%, and 100%), (≤67.69 ng/L, 97.8%, and 100%), and (≤5.38 ng/L, 95.6%, and 95.6%), respectively. In conclusion, serum levels of DAF, TNF-α, and IL-1β have good potential to be used as markers for the assessment of the response to RTX therapy in rheumatoid arthritis patients.